The Effectiveness of Earthquake Disaster Management Policy in Indonesia - Willya Achmad (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Indonesia is highly susceptible to a variety of natural and man-made disasters, including earthquakes, volcanoes, tsunamis, droughts, forest fires, flooding, and landslides. The central government and regional administrations have developed numerous disaster management policies, including earthquake disaster management policies. This study's objective is to assess the efficacy of Indonesia's earthquake management policies. This study employed a qualitative research methodology with a descriptive approach. The results of the study indicate that Indonesia's seismic disaster management policies have been comprehensively and systematically formulated through Law Number 24 of 2007 concerning Disaster Management and its derivatives. Government Regulation Number 21 of 2008 Regarding Disaster Management Implementation. At the stage of implementing earthquake disaster management policies in Indonesia, in general, it has been running effectively. This can be measured from indicators of effective communication, availability of resources, disposition and bureaucratic structure. However, even though it has been running effectively, improvements are still needed, such as in terms of information, infrastructure, budget, coordination between the central and regional governments. From this study it can be concluded that to increase the effectiveness of earthquake management policies, the government can increase access to information, infrastructure and resources for earthquake disaster management.